Fixed-Wing UAVs Flock Control through Cohesion and Repulsion Behaviours Combined with a Leadership. (25th February 2016) - Kownacki, Cezary; Ołdziej, Daniel
The aim of this paper is to present a novel approach to swarm control of small fixed-wing UAVs, which combines only two flocking behaviours with a leadership feature. In the presented approach, two fundamental rules of Reynolds flocking are applied, i.e., cohesion and repulsion, as the base of a decentralized control of self-organization of the flock. These rules are combined with a leadership feature, which is responsible for a global behaviour of guidance, as in the case of animals. Such a bio-inspired combination allows the achievement of a coherent collective flight of a flock of fixed-wing UAVs without applying formal behaviours of migration and alignment. This highly simplifies an implementation of the algorithm. The presented results include both numerical simulations and experimental flights, which validate the hardware implementation of the approach.